2018
DOI: 10.1016/j.jbusres.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic identity, consumer ethnocentrism, and purchase intentions among bi-cultural ethnic consumers: “Divided loyalties” or “dual allegiance”?

Abstract: Consumer ethnocentrism has been studied extensively in international marketing in the context of one's country of residence. This paper investigates for the first time the notion of "dual ethnocentrism", which may be encountered among ethnic consumers who have an allegiance toward, or divided loyalties between, two countries: One with which they are ethnically linked, or "home", and one where they presently live and work, or "host". The study examines the relationship between ethnic identity, dual ethnocentris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 55 publications
6
53
2
1
Order By: Relevance
“…However, it could be interpreted that, being a parallel identity construct to both personal and place identity which is embedded in social identity theory, the link between identity and flow is coherent with our previous findings relating flow with other kinds of identity levels' constructs [23,24,66]. The effect of brand identity on purchase intention, though not yet studied insofar to our knowledge, parallels constructs' effects like self-identity [13], ethical identity [14], and cultural identity [16], which are all connected to purchase intention. In general, therefore, the present result regarding the influential role of brand identity and the flow experience it promotes is coherent with the broader idea of an identity-driven customer engagement predicting purchase intention [10].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, it could be interpreted that, being a parallel identity construct to both personal and place identity which is embedded in social identity theory, the link between identity and flow is coherent with our previous findings relating flow with other kinds of identity levels' constructs [23,24,66]. The effect of brand identity on purchase intention, though not yet studied insofar to our knowledge, parallels constructs' effects like self-identity [13], ethical identity [14], and cultural identity [16], which are all connected to purchase intention. In general, therefore, the present result regarding the influential role of brand identity and the flow experience it promotes is coherent with the broader idea of an identity-driven customer engagement predicting purchase intention [10].…”
Section: Discussionsupporting
confidence: 87%
“…They include, for instance, factors acting brand communication (such as social media advertising [3,4]); factors acting on user's personal experiences toward the product (such as affective, cognitive, behavioral, social and sensory experiences [5]); factors like consumers' optimal experience (i.e., flow, [6]) and users' attitudes [7], which comprise affective components, cognitive components and behavioral components. There are also factors that directly influence purchase intention, for instance, the product's functional and symbolic value dimensions [8]; the brand image of the product [9]; the identity the product represents [10] such as self-identity [11], social identity [12], or both self-and social identity [13], ethnic identity [14,15], and cultural identity [16]; as well as brand personality [17].However, only a few prior studies have demonstrated that not only the optimal experience of flow [18], but also identity (i.e., self-identity, social identity, brand identity) facilitates customers' purchase intention. Moreover, previous studies also indicated that brand-related constructs (i.e., many on brand image, a few only on brand personality and brand communication) influence purchase intention.…”
mentioning
confidence: 99%
“…However, Use of Local Media and Use of Local Language dimensions do not have any significant association with ethnocentrism. The findings of the four positive significant dimensions are consistent with the past findings given in the literature review section (Banna, Papadopoulos, Murphy, Rod, & Mojas-Mendex, 2018; Javalgi et al, 2005; Zarkada-Fraser & Fraser, 2002). However, Use of Local Media and Use of Local Language dimensions had not any significant association with CET for consumers in India.…”
Section: Discussionsupporting
confidence: 90%
“…Ethnocentric consumer trends affect the emotional dimension related to the process of buying foreign products and creates the assumption that this choice somehow threatens domestic industry and national security (Herche, 1992). Thus, ethnocentric consumers believe that buying foreign-produced products is morally wrong and does not contribute to the local economy (El Banna et al, 2018), therefore opting to buy domestic products and disregarding foreign products. With increasing globalization, the concept of ethnocentrism becomes relevant for understanding the moral concern resulting from the consumption of domestic versus foreign goods (Siamagka et al, 2015).…”
Section: Ethnocentrismmentioning
confidence: 99%